An Introspection on the need of medication compliance in geriatric patients with hypertension - Nivya, S; John, Nimmy N; Thomas, Aksa Maria (Journal of Drug Delivery and Therapeutics, 2021)
Introduction: Medication compliance is consequential part of treatment success. Medication non- compliance in geriatric patients leads to substantial worsening of disease, increased healthcare costs, and death.  Financial constraints and adverse events or side effects associated with non-compliance can be avoided by improving medication compliance. Objective: To assess the level of medication compliance in geriatric patients and to analyse factors causing non-compliance to medications. Methods: This cross-sectional study was carried out from May 2020 to July 2020 in a rural area of South India. 150 geriatric patients (aged >60 years) attending the Non- Communicable Disease (NCD) clinics in Primary Health Centres (PHC) were interviewed using validated questionnaires. Results: A total of 150 geriatric participants with Hypertension were assessed for the level of compliance for long term medications. Maximum numbers of participants were males (54%) and majority were found in the age group of 61-70 (42%) and good compliance was observed in 63% of the participants and suggests that the compliance level has decreased progressively with increasing age. Good compliance was seen in subjects with up to 2 medications (55%) compared to more than 2 medications (25%).  The level of compliance was good in 47%, moderate in 35% and poor in 18% of the participants. Conclusion: This study shows poor compliance to the prescribed medication among geriatric subjects with chronic diseases. Different strategies should be used to increase medication compliance in geriatric patients to achieve better outcomes in their health status.Keywords: Medication compliance, Hypertension, geriatric patients